CONVERSION CHEMOTHERAPY FOR LOCALLY ADVANCED RECTAL CANCER: A CASE REPORT - A. Z. Azanov; A. P. Koshel; S. V. Vtorushin; О. V. Zharkova; К. V. Vyalova; I. V. Vikhlyanov; N. Е. Verzhbitskaya; A. S. Lyakhov (Сибирский онкологический журнал, 2016)
We present a case report of locally advanced colorectal cancer that responded successfully to conservation chemotherapy allowing R resection to be performed.   Morphological characteristics prior to and after chemotherapy have been described in detail. This case report demonstrates the feasibility of performing radical treatment for patients with locally advanced rectal cancer using neoadjuvant chemotherapy.